Public Financial Management as an Enabler for Health Financing Reform: Evidence from Free Health Care Policies Implemented in Burkina Faso, Burundi, and Niger - Hélène Barroy; Joseph Kutzin; Seydou Coulibaly; Alexis Bigeard; S Pierre Yaméogo; Jean-François Caremel; Catherine Korachais (Health Systems & Reform, 2022)
AbstractIn Burkina Faso, Burundi and Niger, the policy to remove user fees for primary care was carried out through significant adjustments in public financial management (PFM). The paper analyzes the PFM adjustments by stage of the budget cycle and describes their importance for health financing. The three countries shifted from input-based to program-based allocation for primary care facility compensation, allowed service providers autonomy to access and manage the funds, and established budget performance monitoring frameworks related to outputs. These PFM changes, in turn, enabled key improvements in health financing, namely, more direct funding of primary care facilities from general budget revenue, and payments to those service providers based on outputs and drawn from noncontributory entitlements. The paper draws on these experiences to provide key lessons on the PFM enabling conditions needed to expand health coverage through public financing mechanisms.